“I Knew Him, Horatio”: Shakespeare’s Beliefs, Early Textual Editing, and Nineteenth-Century Phrenology - Bryan Adams Hampton (Religions, 2019)
As Hamlet gazes into Yorick’s skull, he reassembles the quirks of the jester’s personhood and also imagines a self that he used to be, in relation to Yorick. Partially through the lens of Hamlet, characterized by A.C. Bradley as Shakespeare’s most “religious„ play, this essay interrogates how several eighteenth-century textual editors, and some nineteenth-century scholars and popular admirers, imagine and construct Shakespeare’s beliefs: the first, through their efforts to reassemble the textual “bones„ of Shakespeare’s works; and the second, through the rising pseudoscience of phrenology, operating in the background in the national debate to exhume and examine Shakespeare’s skull.